Síntese, caracterização estrutural e análise do potencial catalítico do SrTiO3 e das Perovskitas duplas de Sr1-xKxTiCux/2O3, onde x = 0,2; 0,3 e 0,5, na preparação de biodiesel - Storti, Fernando [UNESP] (2014)
In this work was investigated the synthesis, structural and spectroscopic characterization and the analysis of the catalytic potential of SrTiO3 of perovskita structure and of perovskites doubles Sr1-xKxTiCux/2O3, where x = 0.2, 0.3 and 0.5, in the biodiesel preparation by ethyl route. From the host structure of strontium titanate SrTiO3 were investigated solid solutions containing copper and potassium atoms with the following stoichiometry: Sr0.8K0.2TiCu0.1O3, Sr0.7K0.3TiCu0.15O3 and Sr0.5K0.5TiCu0.25O3, prepared by chemical synthesis using Modified Polyol method. The systems investigated were evaluated using the techniques of thermal analysis (TGA) and differential scanning calorimetry (DSC), scanning electron microscopy (SEM), X-ray diffraction (XRD) and infrared spectroscopy (FTIR). The structural parameters of the investigated systems were determined by the refinement using the Rietveld method, considering the space group Pm m. From the determination of the crystallographic parameter was build the of unit cell of the SrTiO3 using the program Diamond 3.2. The catalytic study was performed from heterogeneous catalysis, with addition of nanoparticles in solution containing vegetable oil and ethyl alcohol. The transesterification process was carried out in a reactor laboratory scale, developed at the LaCCeF, with stirring and controlled temperature. In this process the main products were biodiesel and residual glycerol. During the experiments were controlled the process parameters such as reaction time, catalyst concentration, temperature and stirring degree. In the end of the catalysis reaction was possible to filter and reprocess it to a new reaction, recover the ethanol and calculate the yield of biodiesel from the characterization by gas chromatography coupled to mass spectrometry. The results showed that the Sr0.5K0.5TiCu0.25O3 catalyst is the most efficient for obtention of biodiesel presenting a high conversion in the ...